Evidence in Haemophilia Assessment: The Haemophilia Joint Health Score - Graf, Lukas (Hämostaseologie, 2025)
Haemophilia is a rare genetic bleeding disorder that primarily affects males and results in the deficiency of clotting factors VIII (haemophilia A) or IX (haemophilia B). One of the most debilitating long-term complications of haemophilia is chronic joint damage with pain, and reduced mobility, due to bleeding into the joints. As the primary cause of morbidity in people with haemophilia (PwH), joint health assessment is critical for disease management and optimizing patient outcomes. Among the tools developed to monitor joint health in PwH, the Haemophilia Joint Health Score (HJHS) has emerged as the most widely used and validated clinical tool. There is evidence supporting the use of the HJHS in both children and adults. In contrast to scoring methods that incorporate imaging techniques, which primarily describe the morphology of the joints, the HJHS allows for the assessment and monitoring of joint functionality.
Keywords: haemophilia; joint health; score